The Hydrogen Bond : a Bond for Life. - Hüttermann, Aloys (Walter de Gruyter GmbH, 2019)
The author illustrates why the rather weak hydrogen bond is so essential for our everyday life in a lively and entertaining way. The chemical and physical fundamentals are explained with examples ranging from the nature of water over the secret of DNA to adhesives and modern detergents. The interdisciplinary science is easy to understand and hence a great introduction for chemists, biologists and physicists.- Resumé vydavatel
Keywords: vodíková vazba; chemické vazby; mezimolekulové síly; hydrogen bond; chemical bonds; intermolecular forces; elektronické knihy; monografie; electronic books; monographs